Smart Fertilizing Technologies for Agricultural Efficiency in Canada - Nurhayati Nurhayati; Li Wei; Zhang Li (Techno Agriculturae Studium of Research, 2024)
Canada, amid the growing need for sustainable food production. The background of this research focuses on the challenges of modern agriculture in the efficient use of fertilizers and their impact on the environment. The purpose of the study was to examine the extent to which smart fertilization technology can improve agricultural yields while reducing fertilizer use and environmental impact. The research method used is a quantitative approach with field experiments involving farmers in five major Canadian provinces, using soil and weather sensors to collect data in real-time. The results of the study show that smart fertilization technology is able to increase crop yields by up to 22% and reduce fertilizer use by up to 18%, as well as reduce environmental impact by 9-12%. The conclusion of the study is that smart fertilization technology has great potential in improving agricultural efficiency and maintaining environmental sustainability in Canada. However, more research is needed to understand the long-term impact and ensure equitable access to these technologies across the region.